Artificial intelligence: Concepts, tools and techniques (New York Murphy & Moore Publishing, 2021)
The intelligence exhibited by machines is known as artificial intelligence (AI). The long-term objective of research in AI is to mimic human intelligence. Artificial Intelligence can be classified into artificial general intelligence and artificial biological intelligence. Artificial general intelligence refers to the ability of any intelligent agent to mimic an intellectual task which humans can perform. Artificial biological intelligence aims to understand the natural intelligence of humans. Some of the recent advances in artificial intelligence have been driven by progress in data processing power of modern machines, the use of computational intelligence, statistical methods, and traditional symbolic AI. Some of the tools used include artificial neural networks and mathematical optimization. This book is a valuable compilation of topics, ranging from the basic to the most complex advancements in the field of artificial intelligence. The topics covered herein deal with advanced algorithms as well as the concepts, tools, and techniques that are furthering this discipline. Researchers and students in this field will be assisted by this book.
Keywords: Artificial intelligence; Fifth generation computers; Neural computers